A royalist mathematical practitioner in interregnum Oxford: the exploits of Richard Rawlinson (1616–1668). Issue 3 (27th May 2018) - Poole, William
ABSTRACT: This article explores the biography and career of the forgotten Oxford mathematician and astronomer Richard Rawlinson, 1616-1668. It also identifies both his sole surviving work in an overlooked engraved booklet, and his mathematical manuscripts, still in the library of Queen's College today.